(untitled) (Journal of human and social sciences, 2022)
The technical and vocational education systems in Germany and Japan have played a central role in their post-World War II recovery and economic growth. Germany transformed into a leading industrial nation with high-quality vocational training, supported by substantial investment in education and research, constituting 6.5% of its national budget in 2012. Its dual education system, strong industrial base, and globally competitive exports have reinforced the importance of vocational training as a foundation for sustainable economic development. Similarly, Japan emphasized high-quality education, rigorous teacher selection, and training systems that promote critical thinking over rote memorization, producing a highly skilled workforce that drives technological innovation and economic competitiveness. Japanese education integrates cultural values, societal cohesion, and technological advancement, creating balanced and highly capable graduates. This study highlights the economic and social significance of vocational and technical education as a means of preparing skilled human resources to meet labor market demands, reduce unemployment, and enhance national development. It also addresses challenges faced by Libya, where technical education outputs often fail to meet market needs. The study adopts a descriptive-analytical approach, examining Germany and Japan’s models and drawing lessons for Libya. Key objectives include understanding the development of technical education in these countries, analyzing their systems, and extracting strategies and recommendations to improve Libya’s technical education and better align it with labor market requirements